PERAN E-MEDIA INTERAKSI DALAM MENINGKATKAN MUTU PEMBELAJARAN: STUDI KASUS PEMILIHAN DAN IMPLEMENTASI DI LEMBAGA PENDIDIKAN ISLAM - Maya Delpita; Dewi Andriani; Titi Herlina; Novita Sari; Ismail Syakban (Ensiklopedia of Journal, 2026)
The development of interactive e-media offers significant opportunities for improving the quality of learning in Islamic Educational Institutions (LPIs), but its use must be aligned with Islamic values and the curriculum of Islamic boarding schools (pesantren) or madrasahs. This research is crucial because there is still a gap between advances in educational technology and LPIs' readiness to integrate it optimally. This research employed a qualitative case study approach, involving in-depth interviews with teachers and administrators, classroom observations, and document analysis related to the use of digital media. The results indicate that interactive e-media can increase learning motivation, enrich understanding of the material, and support more adaptive learning. However, challenges such as limited infrastructure, integration of Islamic values, and teacher competency still require attention. Overall, interactive e-media can effectively improve the quality of LPI learning if planned and implemented strategically and sustainably.Keywords: Islamic Interactive E-Media; Islamic Digital Learning Transformation; Multimedia Interactivity; Islamic Pedagogical Innovation; Smart Learning for Students